The History of the Brazilian Sardine (Sardinella brasiliensis) Between Two Fishery Collapses: An Ecosystem Modeling Approach to Study Its Life Cycle - Rafael Schroeder; Angélica Petermann; Alberto Teodorico Correia (Biology)
The inter-annual fluctuations of abundance of the Brazilian sardine (Sardinella brasiliensis) during the last decades have deeply modified the purse seine fishery dynamics. This study evaluates the trophic relationships of the main species exploited by this fishery and the importance of its biomass for the southeast–south Brazil marine ecosystem (22° S–34° S). Data were analyzed using a mass balance model (ECOPATH) between the two fishery collapses: 2000 and 2017. From 2000 onwards, the sardine fishery adopted a multi-species character. The mean trophic level of the catches (MTL) showed a decreasing trend until 2008, when more modern vessels with greater autonomy entered the fishery, and expanded the traditional fishing area to exploit northern fishing grounds. The MTL in the expanded fishing area suddenly increased and was characterized by high biomass of the Brazilian sardine and other species with a high biomass and high ecotrophic impact, falling again to the lowest level in 2016. The model evidenced high estimates for fishing mortality, natural mortality, and flow to detritus between 2008 and 2016, when sardine fishing collapsed. During this period, a sharp drop in the primary production required to sustain the catches from 2012 onwards accompanied a significant fall in the biomass accumulation rate. This pattern was coincidental with the increasing mean temperature of the catches, which was probably acting as a limiting factor for the primary production, resulting in a higher natural mortality and flow to detritus. Furthermore, the higher fishing mortality may have led the stock to collapse.